Unravelling Africa's raw material footprints and their drivers - Albert Kwame Osei-Owusu; Michael Danquah; Edgar Towa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper applies an environmentally extended input-output analysis, leveraging the Eora database, to estimate the global raw material footprints of 51 African nations from 1995 to 2015. It employs least absolute shrinkage and selection operator and panel regression models to quantify the effects of diverse variables on Africa's raw material footprints. The findings show that the raw material footprints of Africa's production and consumption soared by 41 per cent and 38 per cent, respectively, from 1995 to 2015, mainly driven by biomass and construction materials. They show that Africa outsources 25 per cent of its raw material footprints from consumption, while over 60 per cent of its footprints from production arise from its exports. Our findings beckon African governments to reduce the excessive focus on exploitation and concentrate on combatting corruption and extreme rent-seeking while decoupling Africa's raw material footprints from rising public debt, carbon emissions, income levels, and population.
Keywords: C33; C67; F18; 330; Eora database; material footprints; input-output analysis; least absolute shrinkage and selection operator model; Africa